AFRICAN MUSIC IN GHANA by J. H. KWABENA NKETIA. Pp. 148 including 30 pp. music transcription and 2 maps. Longmans, 1962. - Jones, A. M. (International Library of African Music, 1962)
pages: 116
Keywords: African Music; Ghana